Clinical Effectiveness of Neoadjuvant Chemotherapy in Gastric Carcinoma and Exploration of Perioperative Imaging Assessment Parameters - Jiajun Lai; Junsheng Li; Xianwei Mo (Gastroenterology Research and Practice)
Background and Aims. Due to the difficulty in clinical staging, a simple and feasible perioperative assessment approach for guiding personalized neoadjuvant chemotherapy (NAC) is lacking. We investigated the clinical value of NAC in advanced gastric carcinoma (GC) and the concordance between perioperative imaging and postoperative pathological assessments. Methods. This study included 62 patients with advanced GC who received NAC between January 2012 and December 2018. The preoperative and postoperative T stages, postoperative pathological tumor regression grade (TRG), and changes in computed tomography (CT) values after NAC were assessed. Follow-ups were conducted to obtain the median survival time (MST), and Kaplan–Meier survival curves were plotted. Results. The T stages significantly differed between before and after NAC (p=0.001). The MST of patients in the TRG0 group was significantly different from that of patients in the TRG1+2 and TRG3 groups (p=0.223). The percentages of positive lymph nodes were 0%, 24.17%, and 27.64% in the TRG0, TRG1+2, and TRG3 groups, respectively. TRG was correlated with changes in CT values before and after NAC, and the extent of change was associated with patient prognosis. Conclusions. Perioperative imaging can be used to assess the short-term effectiveness of NAC for patients with GC.